Soil texture and structure heterogeneity predominantly governs bulk density gradients around roots. Issue 5 (8th July 2021) - Phalempin, Maxime; Lippold, Eva; Vetterlein, Doris; Schlüter, Steffen
Abstract: Rhizosphere soil is known to differ from the bulk soil due to numerous physicochemical processes induced by root growth. The spatial extent and magnitude of the influence of roots on the surrounding soil is still debated controversially. To date, most studies focused on a limited number of soil types and plant species and were carried out under homogeneous soil structure conditions (i.e., finely sieved and repacked soil). With the help of X‐ray computed tomography (CT), we present the results of an image processing workflow, which enabled to analyze soil structure around roots of maize ( Zea mays L.) plants under different degrees of soil structure heterogeneity. We analyzed >400 samples extracted during laboratory and field experiments covering various combinations of texture, bulk density, packing heterogeneity, maize genotype, and soil moisture. We show that soil texture and structure heterogeneity predominantly governs the magnitude of bulk density alteration around roots. In homogeneous soil structure, roots had to create their own pores by pushing away soil particles, which confirms previous findings. Under more heterogeneous conditions, we found that roots predominantly grew in existing pores without inducing compaction. The influence of root hairs, root length density, and plant growth stages had no or little impact on the results. The effect of root diameter was more pronounced in sand than in loam. Fine roots caused sand grains to align along their axis, whereas big roots broke the fragile arrangement of grains. Our findings have implications for water and solute transport dynamics at the root–soil interface, which may affect plant productivity. Core ideas: Roots rearrange soil particles during ingression into the soil. Bulk density distribution around roots is predominantly governed by soil texture and structure. Our findings have implications for water and solute transport at the root–soil interface.